PENGARUH PENDAPATAN ASLI DESA (PADESA), DANA DESA (DD), BAGI HASIL PAJAK dan RETRIBUSI (BHPR) TERHADAP BELANJA DESA (STUDI KASUS KECAMATAN ADONARA BARAT KABUPATEN FLORES TIMUR TAHUN ANGGARAN 2015-2016) - Sumiati, Waloo; Made, Anwar; Mustikowati, Rita Indah (Jurnal Riset Mahasiswa Akuntansi, 2017)
The Village Budget (APBDesa) provided by the central government as financing village activities to increase the level of public welfare. The Village Budget (APBDesa) consists of Village income, village expenditure, financing. Village income sources are village income, transfer funds grants and third party donations that are not binding, other original village income. The purpose is to examine the effect of original village income, village funds, tax sharing and user fees on village spending. The population is Adonara Barat District, East Flores Regency, Fiscal Year 2015-2016. The sample of all villages in Adonara Barat Subdistrict, East Flores Regency is 18 villages. The analytical tool is multiple linear regression analysis. The results are; (1) village original income, village funds, tax revenue sharing and levies on village expenditure simultaneously have a significant effect on village spending. (2) village original income significantly influences village expenditure. (3) village funds have a significant effect on village spending. (4) tax and retribution sharing has a significant effect on village expenditure.